2016
DOI: 10.1536/ihj.16-054
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of the Relationship Between Maternal Folic Acid Supplementation and the Risk of Congenital Heart Defects

Abstract: SummaryControversial opinions exist with respect to the relationship between maternal folic acid (FA) supplementation and birth prevalence of congenital heart defects (CHDs).Eligible articles were retrieved by searching databases, including PubMed, Cochrane library, EMBASE, CNKI, and WanFang up to September 2015. A meta-analysis was performed to evaluate the effects of FA on CHDs. Odds ratios (ORs) and 95% confidence interval (CIs) were merged using STATA 12.0. Meta-regression analysis was used to explore the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 34 publications
1
36
0
Order By: Relevance
“…This metabolite is not only directly toxic against the dividing cells but also increases ROS level As a result, the developmental process of embryos can be disrupted secondary to intracellular FA shortage. Considering that, an association already exists between FA deficiency and an increased risk of congenital anomalies in the absence of DM . DM by itself may further worsen preexisting and therefore increases the rate of anomalies.…”
Section: The Potential Underlying Pathophysiology For Birth Defectsmentioning
confidence: 99%
See 2 more Smart Citations
“…This metabolite is not only directly toxic against the dividing cells but also increases ROS level As a result, the developmental process of embryos can be disrupted secondary to intracellular FA shortage. Considering that, an association already exists between FA deficiency and an increased risk of congenital anomalies in the absence of DM . DM by itself may further worsen preexisting and therefore increases the rate of anomalies.…”
Section: The Potential Underlying Pathophysiology For Birth Defectsmentioning
confidence: 99%
“…DM by itself may further worsen preexisting and therefore increases the rate of anomalies. Moreover, previous studies demonstrated that FA supplementation can decrease the incidence of diabetes‐induced congenital abnormalities . Understandably, FA deficiency is obviously not the only factor explaining the pathogenesis of diabetic embryopathy, but can take part in the pathogenesis.…”
Section: The Potential Underlying Pathophysiology For Birth Defectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, connecting folic acid to these outcomes lacks a strong biological and mechanistic premise. In some cases, folate intakes from all sources at or above the recommended dietary allowance and/or maintenance of adequate folate status have been shown to be protective for these and related outcomes …”
Section: Safety Of Folic Acidmentioning
confidence: 99%
“…If not complete by day 28, this results in neural tube defects (NTD) such as spina bifida, anencephaly, and encephalocele. Moreover, several studies suggest the risk for congenital anomalies of other structures requiring integration of migrating neural crest cells, such as the heart and the lip/palate, can also be decreased by maternal FA supplementation 15 . After about eight weeks cardiac outflow tracts and septation that depend on neural crest cells are complete.…”
Section: Introductionmentioning
confidence: 99%